PENGARUH KEBIJAKAN HUTANG TERHADAP GROWTH OPPORTUNITY, KEPUTUSAN INVESTASI DAN NILAI PERUSAHAAN PADA PERUSAHAAN YANG TERDAFTAR DI INDEX LQ 45 DI BURSA EFEK INDONESIA (BEI) PERIODE 2012-2015 - Maria, Evi (DINAMIKA DOTCOM, 2019)
One of the company's main goals is to maximize company value. Company value is an investor's perception of the level of company success that is often associated with stock prices. This research aims to analyze the influence of debt policy toward growth opportunity, investment decisions, and company value. Moreover, this researching on companies listed on the LQ 45 Index on the Indonesia Stock Exchange for the period 2012-2015. The analysis method used structural equation analysis / SEMPLS with the help of SmartPLS version 2 software. The results of this research indicate that debt policy has a significant influence partially toward growth opportunity with a t-statistic value of 4,453136 (> 1.96). However, debt policy has not a significant influence on firm value with a t-statistic value of 1.387508 (<1.96). And also, Growth Opportunity has a significant influence partially toward firm value with a t-statistic value of 3.286849 (> 1.96). While Growth Opportunity has not a significant influence on investment decisions with a t-statistic value of 0.277165 (<1.96).Investment decisions have a significant influence partially on firm value with a t-statistic value of 4.175537 (> 1.96). The coefficient of determination (R2) of debt policy towards growth opportunity, investment decisions, and company value is 0.040; 0.001 and 0.349.Keywords: debt policy, growth opportunity, investment decisions, and company value